The Poincare-Mel’nikov geometric analysis of the transversal splitting of manifolds of slowly perturbed nonlinear dynamical systems. I - Prykarpatsky, A. K.; Samoilenko, A. M.; Timchishin, O. Ya. (Ukrains’kyi Matematychnyi Zhurnal, 1993)
On the basis of the geometric ideas of Poincaré and Mel’nikov, we study sufficient criteria of the transversal splitting of heteroclinic separatrix manifolds of slowly perturbed nonlinear dynamical systems with a small parameter. An example of adiabatic invariance breakdown is considered for a system on a plane.